NEW VARIETY OF WINTER BARLEY ‘EREMA’ - E. G. Filippov (Зерновое хозяйство России, 2018)
Barley is one of the basic grain forage crop. About 80% of the barley yields are used as forage. Russia ranks second in the barley production after the EC-27 countries. The Southern Federal District, where Rostov region is located, produces 15% of total barley production in Russia. The hybridization of varieties tolerant to winter, drought, lodging and diseases is one of the main task of winter barley breeding in All-Russian Research Institute of Grain Crops after I.G. Kalinenko. The article considers morphological and economic-biological characteristics of the new winter barley cultivar ‘Erema’, hybridized in the department of breeding and seed-growing of winter and spring barley of ARRI of Grain Crops after I.G. Kalinenko using the method of intraspecific complex gradual hybridization.  The new cultivar was included in the State Register of Selection Achievements of RF in 2015 for six regions. The variety is used for forage. The type of the development is winter. ‘Erema’ is characterized by high features of winter tolerance, resistance to lodging and productivity. During variety testing (2012-2014) the average productivity of the cultivar was 6,9 t/ha, which was 1,2 t/ha more than the standard variety ‘Master’ produced. Introduction of winter wheat variety ‘Erema’ will allow stabilizing grain production in the south of Russia.